2012
DOI: 10.1115/1.4007714
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Vibration-Assisted Nano-Impact Machining by Loose Abrasives Using Atomic Force Microscope

Abstract: Nanomachining of brittle materials is required in a wide range of applications. This paper reports on the feasibility studies of" vibration-assisted nano-impact machining by loose abrasives (VANILA), a novel nanomachining process for target-specific nanomachining of hard and brittle materials. A mathematical model based on Hertzian fracture mechanics theory has been developed to evaluate the feasibility of material removal in the VANILA process, where hard abrasive grains impact the brittle workpiece suiface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Fig.18. shows the material removal by abrasives where less unit material removal is achieved with high precision surface finish [30], further the tool wear is significantly reduced [31,32]. …”
Section: Vibration Assisted Abrasive Machining (Vaam)mentioning
confidence: 96%
“…Fig.18. shows the material removal by abrasives where less unit material removal is achieved with high precision surface finish [30], further the tool wear is significantly reduced [31,32]. …”
Section: Vibration Assisted Abrasive Machining (Vaam)mentioning
confidence: 96%
“…VANILA, a tip-based nanomachining process that uses a single-point AFM probe with loose abrasives and vibration assis tance, has the potential to perform target specific impact-based machining of nanoscale features on hard and brittle materials, such as glass and ceramics [5], This process uses an AFM plat form in which a slurry of nanodiamond abrasive particles is intro duced between the tool and the workpiece. The machining is conducted in tapping mode where the tool vibrates at resonance within the slurry of abrasive nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies using scanning electron microscopy (SEM) imaging have shown that tool wear in the VANILA process is comparatively lower than that in other nanomachining processes such as nanoscratching and nanoindentation involving direct tool contact with the workpiece (Figure 3) [2]. The accuracy and precision of any tip-based nanomachining process is limited by the tip's sharpness, material, and geometry [3].…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of nanocavities were successfully machined to demonstrate the controllability and repeatability of the process as shown in Figure 2 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation